Preferential formation of sodium salts from frozen sodium-ammonium-chloride-carbonate brines – Implications for Ceres' bright spots. (July 2017) - Vu, Tuan H.; Hodyss, Robert; Johnson, Paul V.; Choukroun, Mathieu
Abstract: Observations of bright deposits in Ceres' Occator crater have revealed large quantities of natrite (Na2 CO3 ) and smaller amounts of NH4 Cl or NH4 HCO3 . These materials have been suggested to originate from the crystallization of brines that reached the surface from below. Here we report a systematic study of the chemistry of frozen brines containing sodium, ammonium, chloride, and carbonate ions via micro-Raman spectroscopy. Natrite and hydrohalite (NaCl·2H2 O) are found to form preferentially, even in ammonium-dominated solutions. Additionally, NH4 Cl could only form when NH4 + or Cl - (or both) are present in excess in the brine solutions. The detection of NH4 Cl on Ceres' surface may thus imply an early subsurface reservoir rich in ammonium and/or chloride, placing an important constraint on modeling of the liquid composition. Highlights: Sodium salts preferably form on freezing of brines containing Na +, NH4 +, Cl -, CO3 2- . Natrite (Na2 CO3 ) forms and remains stable even in brines dominated by NH4 + or Cl - . NH4 Cl in bright spots may imply a subsurface reservoir rich in NH4 + and/or Cl - .